8 - Privatization of Water and Sanitation Services in Kenya: Challenges and Prospects - Nyangena, Kenneth O. (Africa Development, 2021)
Public sector utilities in developing countries have often not been efficient in providing access to reliable water and sanitation services. Worldwide, over 1 billion people lack access to improved water sources and 2.6 billion lack access to appropriate sanitation.1 Countries across the world are increasingly looking to the private sector for help in providing needed water services. Towards this end, privatization of water and sanitation services is viewed to be a cost effective method of service delivery that also enhances quality and performance. This paper seeks to highlight general knowledge, attitudes and practices of privatiza- tion of the service providers in the water and sanitation sector. It also underlines current challenges in the management of privatization of water and sanitation services in Kenya on the part of service providers, but also consumers. The most common challenges include inequity in the quality of service based on the ability to pay, service cut-offs, weak regulatory oversight and lack of accountability to local consumer needs. This paper shows that there is, however, consensus among water and sanitation service providers that privatization is likely to improve effi- ciency in water and sanitation services only if a collaborative effort is embraced in tackling public sector reform in Kenya. The paper also provides recommendations towards achieving privatization of water and sanitation services.